Sustainable volume sweep imaging lung teleultrasound in Peru: Public health perspectives from a new frontier in expanding access to imaging - Marini, Thomas J.; Castaneda, Benjamin; Satheesh, Malavika; Zhao, Yu T.; Reátegui-Rivera, C. Mahony; Sifuentes, Walter; Baran, Timothy M.; Kaproth-Joslin, Katherine A.; Ambrosini, Robert; Rios-Mayhua, Gloria; Dozier, Ann M. (Frontiers in Health Services, 2023)
Background: Pulmonary disease is a common cause of morbidity and mortality, but the majority of the world lacks access to diagnostic imaging for its assessment. We conducted an implementation assessment of a sustainable, cost-effective model for delivery of volume sweep imaging (VSI) lung teleultrasound in Peru. This model allows image acquisition by individuals without prior ultrasound experience after only a few hours of training. Methods: Lung teleultrasound was implemented at 5 sites in rural Peru after a few hours of installation and staff training. Patients were offered free lung VSI teleultrasound examination for concerns of respiratory illness or research purposes. After ultrasound examination, patients were surveyed regarding their experience. Health staff and members of the implementation team also participated in separate interviews detailing their views of the teleultrasound system which were systematically analyzed for key themes. Results: Patients and staff rated their experience with lung teleultrasound as overwhelmingly positive. The lung teleultrasound system was viewed as a potential way to improve access to imaging and the health of rural communities. Detailed interviews with the implementation team revealed obstacles to implementation important for consideration such as gaps in lung ultrasound understanding. Conclusions: Lung VSI teleultrasound was successfully deployed to 5 health centers in rural Peru. Implementation assessment revealed enthusiasm for the system among members of the community along with important areas of consideration for future teleultrasound deployment. This system offers a potential means to increase access to imaging for pulmonary illness and improve the health of the global community.